Challenging Isomorphism: Institutional Responses and Regulative–Professional Logical Tensions in Tourism Higher Education in the Era of Industry - Yudistira, Sukma; Damanik, Janianton; Widyaningsih, Yulia Arisnani; Yusuf, Mohammad (Technium Social Sciences Journal, 2026)
This study examines the institutional responses of tourism higher education institutions (THEIs) in Indonesia to the evolving tourism industry ecosystem during the era of the Industrial Revolution 4.0. Grounded in institutional theory, this study critiques the assumption of isomorphism, which states that external pressures yield uniform responses. Employing a qualitative, multi-case study design, data were gathered through in-depth interviews, institutional documents, and educational policies from three THEIs. The analysis utilized the framework of coercive, normative, and mimetic pressures, alongside the interaction between regulative and professional logic. The findings reveal that although THEIs encounter relatively uniform regulative pressures, particularly through the Independent Learning–Independent Campus (MBKM) policy, institutional responses range from symbolic compliance to substantive adaptation to regulative pressures. The predominance of regulative logic fosters a tendency toward administrative legitimacy, while professional logic derived from the industry remains fragmented and not yet strongly institutionalized. The cross-case analysis identifies three institutional adaptation profiles that underscore the role of internal capacity and adaptive leadership in mediating institutional pressure. This study contributes to the advancement of institutional theory by illustrating that institutional pressures in developing countries operate asymmetrically, reinforcing existing practices and decoupling them in higher education.